Income inequality in today's China - Xie, Yu; Zhou, Xiang (Proceedings of the National Academy of Sciences - PNAS, 2014)
Using multiple data sources, we establish that China's income inequality since 2005 has reached very high levels, with the Gini coefficient in the range of 0.53-0.55. Analyzing comparable survey data collected in 2010 in China and the United States, we examine social determinants that help explain China's high income inequality. Our results indicate that a substantial part of China's high income inequality is due to regional disparities and the rural-urban gap. The contributions of these two structural forces are particularly strong in China, but they play a negligible role in generating the overall income inequality in the United States, where individual-level and family-level income determinants, such as family structure and race/ethnicity, play a much larger role.